Multiple Myeloma-Associated Kidney Disease Complicated by Sudden Death in a 68-Year-Old Man - Victoria L. Ogala-Akogwu; Peter K. Uduagbamen; Habib Galadanci; Emmanuel A. Anteyi (Assam Journal of Internal Medicine)
Kidney disease can complicate multiple myeloma, and this carries a poor prognosis. The multidisciplinary management involves the use of some cardiotoxic drugs which could be fatal. We present the management of a 68-year-old man with chronic back pain, recurrent vomiting, numbness, and tingling sensation for 4 weeks. He had proteinuria, anemia, hypercalcemia, hyperuricemia, serum and urinary paraproteins, lytic bone lesions, and bone marrow plasmacytosis. He was managed for multiple myeloma-associated kidney disease with rehydration, lenalidomide, dexamethasone, antibiotics, and hemodialysis. He became stable and continued treatment till he died suddenly in his sleep. A detailed cardiovascular assessment and drugs pharmacodynamics is essential to prevent sudden death.